Extravascular gelation shrinkage-derived internal stress enables tumor starvation therapy with suppressed metastasis and recurrence - Zhang, Kun (Nat Commun, 2019)
Despite the efficacy of current starvation therapies, they are often associated with some intrinsic drawbacks such as poor persistence, facile tumor metastasis and recurrence. Herein, we establish an extravascular gelation shrinkage-derived internal stress strategy for squeezing and narrowing blood vessels, occluding blood & nutrition supply, reducing vascular density, inducing hypoxia and apoptosis and eventually realizing starvation therapy of malignancies. To this end, a biocompatible composite hydrogel consisting of gold nanorods (GNRs) and thermal-sensitive hydrogel mixture was engineered, wherein GRNs can strengthen the structural property of hydrogel mixture and enable robust gelation shrinkage-induced internal stresses. Systematic experiments demonstrate that this starvation therapy can suppress the growths of PANC-1 pancreatic cancer and 4T1 breast cancer. More significantly, this starvation strategy can suppress tumor metastasis and tumor recurrence via reducing vascular density and blood supply and occluding tumor migration passages, which thus provides a promising avenue to comprehensive cancer therapy.